2019
DOI: 10.1111/jvh.13052
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of hepatitis B virus mutants associated with vaccine escape, drug resistance and diagnosis failure

Abstract: Summary The massive implementation of the vaccine and antiviral agents against hepatitis B virus (HBV), targeting the envelope and viral polymerase genes, induces a selection pressure that might lead to the emergence of variants that impair the effectiveness of the vaccine, diagnostic methods and antiviral therapy. The aim of this study was to evaluate the prevalence of HBV vaccine escape mutants (VEMs), diagnostic failure mutants (DFMs) and treatment resistance mutants (ARMs) among individuals from Buenos Air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 71 publications
5
11
0
Order By: Relevance
“…Overall, immune escape mutations were detected in 10.7% HBV genomes. Similar rates have been determined in cohorts from Argentina (7.5-10.7%) (Di Lello et al, 2019), China (9.01%) (Yan et al, 2017), Spain (6.6-12.5%) (Avellon and Echevarria, 2006), and Turkey (8.3%) (Sayan et al, 2010). Only 4 of the 25 escape mutations had total frequencies of ≥1% (I/T126S, 1.8%; G145R, 1.2%; M133T, 1.2%; and Q129R, 1.0%), consistent with a previous large-scale analysis showing frequencies of no less than 1% for most escape mutations (Ma and Wang, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…Overall, immune escape mutations were detected in 10.7% HBV genomes. Similar rates have been determined in cohorts from Argentina (7.5-10.7%) (Di Lello et al, 2019), China (9.01%) (Yan et al, 2017), Spain (6.6-12.5%) (Avellon and Echevarria, 2006), and Turkey (8.3%) (Sayan et al, 2010). Only 4 of the 25 escape mutations had total frequencies of ≥1% (I/T126S, 1.8%; G145R, 1.2%; M133T, 1.2%; and Q129R, 1.0%), consistent with a previous large-scale analysis showing frequencies of no less than 1% for most escape mutations (Ma and Wang, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…A study performed in Argentina that analyzed HBsAg and HBVPol sequences from 530 samples of HBV-infected individuals found that diagnostic failure mutants (DFM) and vaccine escape mutants (VEM) were detected in 10.7% and 7.5%, respectively. The most frequent DFM was Y100C in subgenotype A1 and was frequently detected in HBsAg negative samples [ 172 ]. Despite that, even if this mutation has been frequently identified in the lack of HBsAg detection in serum samples, in vitro assays suggested that this substitution alone is not enough to evade HBsAg detection by commercial ELISA assay [ 173 ].…”
Section: Viral Epitopesmentioning
confidence: 99%
“…A recent study showed that HBV mutants associated with vaccine escape, diagnosis failure, and drug resistance could be genotypic and sub-genotypic specific. 44 Further studies should be done to assess the impact of anti-HBV therapies on the incidence and spread of HBV escape mutants.…”
Section: Discussionmentioning
confidence: 99%